Quantifying Thematic Saturation in Qualitative Data Analysis. Issue 3 (August 2018) - Lowe, Andrew; Norris, Anthony C.; Farris, A. Jane; Babbage, Duncan R.
An important aspect of qualitative research is reaching saturation—loosely, a point at which observing more data will not lead to discovery of more information related to the research questions. However, there has been no validated means of objectively establishing saturation. This article proposes a novel quantitative approach to measuring thematic saturation based on a sound statistical model. The model is validated on two data sets from different qualitative research projects involving interviews, focus groups, and literature surveys. The proposed model provides consistent estimates of saturation across data sets, within branches of data sets, and over the course of a research project. The model can be used for both quantifying saturation and estimating the number of observations required to achieve a specified level of saturation.